2017
DOI: 10.1002/jssc.201700245
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of γaminobutyric acid in equine plasma by hydrophilic interaction liquid chromatography with tandem mass spectrometry

Abstract: γ-Aminobutyric acid is the principal inhibitory neurotransmitter in the central nervous system and regulates the neuronal excitability. There has been anecdotal evidence that γ-aminobutyric acid has been used within a few hours prior to competition in equine sports to calm down nervous horses. However, regulating the use of γ-aminobutyric acid is challenging because it is an endogenous substance in the horse. γ-Aminobutyric acid is usually present at low ng/mL levels in equine plasma; therefore, a sensitive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…6 A growing body of research describes GABA as an important modulator in cells of the immune system, 13 which is present in nanomolar concentrations in the blood. 14 Our group has demonstrated that nanomolar concentrations of GABA A R allosteric ligands and GABA are sufficient to change the transmembrane current of isolated mouse CD4 + T cells. 7 Oral administration of allosteric GABA A R ligands reduced the number of lung inflammatory cells in ovalbumin-sensitized and challenged asthmatic mice.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 A growing body of research describes GABA as an important modulator in cells of the immune system, 13 which is present in nanomolar concentrations in the blood. 14 Our group has demonstrated that nanomolar concentrations of GABA A R allosteric ligands and GABA are sufficient to change the transmembrane current of isolated mouse CD4 + T cells. 7 Oral administration of allosteric GABA A R ligands reduced the number of lung inflammatory cells in ovalbumin-sensitized and challenged asthmatic mice.…”
Section: ■ Introductionmentioning
confidence: 99%